Nobles in Nineteenth-Century France The Practice of Inegalitarianism - Higgs, David (Johns Hopkins University Press, 2019)
Originally published in 1987. David Higgs's Nobles in Nineteenth-Century France: The Practice of Inegalitarianism provides a history of the nobility against the backdrop of changing French political conditions following the French Revolution. Since Jean Juarès, the influential historian of the French Revolution, many writers have argued that the French Revolution marked the political triumph of a capitalist bourgeoisie over a landed aristocracy. However, beginning with Alfred Cobban, some historians began to question this account by focusing on the continued presence of the nobility in France. This book contributes to this body of work by giving a panorama of the French nobility and three detailed case studies of noble families; the author then concludes with an examination of the nobility in political life, the church, and the private sphere. Professor Higgs finds that French nobles changed with their century, but given their small numbers in the national population, they maintained a grossly disproportionate presence in politics, in culture, among the wealthiest landowners, and in economic life.